Super freakonomics : global cooling, patriotic prostitutes, and why suicide bombers should buy life insurance - Levitt, Steven D.; Dubner, Stephen J. (United Kingdom : Penguin Books, 2009)
Whether investigating a solution to global warming or explaining why the price of oral sex has fallen so drastically, Levitt and Dubner mix smart thinking and great storytelling to show how people respond to incentives.
Introduction: Putting the freak in economics -- How is a street prostitute like a department-store Santa? -- Why should suicide bombers buy life insurance? -- Unbelievable stories about apathy and altruism -- The fix is in--and it's cheap and simple -- What do Al Gore and Mount Pinatubo have in common? -- Epilogue: Monkeys are people too.
Keywords: Economics -- Psychological aspects; Economics -- Sociological aspects; Large type books